Creation of the Continuing Education Program of University of Costa Rica, Western Campus: Challenges and Achievements - Vargas Solís, María Antonieta (2020)
This article is a systematization of experiences on the Continuing Education Program of the Western Headquarters of the University of Costa. The objective is to present the challenges and achievements of the first year of work. Five steps were used for the methodology: Departure Point, Initial Questions, Rebuilding the lived Process, Reflection, and Arrival Points. In the reflection step, it is explained why the changes occurred in terms of geographic location, project target population, program objectives, and administrative management issues. The greatest achievement of the program was to offer more courses than those established in the objectives, and its greatest challenge was to deal with the administrative management involved in opening such a program.